2016
DOI: 10.3892/ijmm.2016.2467
|View full text |Cite
|
Sign up to set email alerts
|

ATP-sensitive K+ channels contribute to the protective effects of exogenous hydrogen sulfide against high glucose-induced injury in H9c2 cardiac cells

Abstract: Hyperglycemia, as well as diabetes mellitus, has been shown to impair ATP-sensitive K+ (KATP) channels in human vascular smooth muscle cells. Hydrogen sulfide (H2S) is also known to be an opener of KATP channels. We previously demonstrated the cardioprotective effects exerted by H2S against high-glucose (HG, 35 mM glucose)-induced injury in H9c2 cardiac cells. As such, we hypothesized that KATP channels play a role in the cardioprotective effects of H2S against HG-induced injury. In this study, to examine this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
34
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 52 publications
5
34
0
1
Order By: Relevance
“…The cells were pre-treatment with 1 mM NAC for 60 min before exposure to HG for 24 h or co-treated with 30 µM TAK-242 or 100 µM Nec-1 and HG for 24 h. Similar to the anti-cytotoxicity effect of the opening of K ATP channels [7], the results of CCK-8 assay (Fig. 5) showed that pre-treatment of the cells with NAC or co-treatment of the cells with TAK-242 or Nec-1 dramatically blocked the HG-induced cytotoxicity, leading to an increase in cell viability, indicating the involvement of ROS-TLR4-necroptosis pathway activation in the HG-induced cytotoxicity.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The cells were pre-treatment with 1 mM NAC for 60 min before exposure to HG for 24 h or co-treated with 30 µM TAK-242 or 100 µM Nec-1 and HG for 24 h. Similar to the anti-cytotoxicity effect of the opening of K ATP channels [7], the results of CCK-8 assay (Fig. 5) showed that pre-treatment of the cells with NAC or co-treatment of the cells with TAK-242 or Nec-1 dramatically blocked the HG-induced cytotoxicity, leading to an increase in cell viability, indicating the involvement of ROS-TLR4-necroptosis pathway activation in the HG-induced cytotoxicity.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, a previous study has indicated diabetes mellitus (DM) is associated with the dysfunction of cardiovascular K ATP channels [17]. More recently, we have demonstrated that high glucose (35 mM glucose, HG) significantly decreases the expression level of K ATP channels and that the opening of K ATP channels protects against the HG-induced injuries, including over-production of reactive oxygen species (ROS) in H9c2 cardiac cells [7]. However, what are the influences of these important channels on the HG-triggered intracellular signaling mechanisms is far less understood.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The activation of KATP channels by H2S has been shown as the mechanism underlying the inhibitory effects of this mediator in a variety of experimental approaches, including aspirin-induced leukocyte adherence in mesenteric venules [48] and high glucose-induced cardiac cells injury [51]. However, this not seem to be the cause beyond the protective effects of the spontaneous H2S donors against histamine-induced pruritus and skin inflammation, as pretreatment of mice with glibenclamide, a selective KATP channels blocker, did not antagonize the protective effects of H2S, even when used at doses that abolish the vasodilatation induced in the mouse dorsal skin by the KATP channel opener pinacidil.…”
Section: Discussionmentioning
confidence: 99%